Śaṅkara-sarvasva : kavi Svargīya Paṇ. Nāthūrāma Śaṅkara Śarmā kī kavitāoṃ kā saṅgraha - Śarmā, Nāthūrāmaśaṅkara, 1859-1932 (SAMP early 20th-century Indian books project, 1951)
Collection of the works of Nāthūrāmaśaṅkara Śarmā, 1859-1932, Hindi poet.